2016
DOI: 10.1039/c5ra23535a
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical assisted synthesis of size and shape tunable gold nanoparticles and assessment of their catalytic activities

Abstract: A faster and environmentally viable phytochemical assisted reduction method of synthesizing catalytically active gold nanoparticles (GNPs) is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…The amount of total phenolics in the flower extract of Lantana Camara plants were determined with the Folin-Ciocalteu reagent using gallic acid as a standard following our previously reported method. [25] A calibration curve was plotted (R 2 = 0.994) with the series of gallic acid standards from which the total phenolic contents values were determined. Results are expressed as mg of gallic acid equivalents (GAE).…”
Section: Isolation Of Flower Extractmentioning
confidence: 99%
See 4 more Smart Citations
“…The amount of total phenolics in the flower extract of Lantana Camara plants were determined with the Folin-Ciocalteu reagent using gallic acid as a standard following our previously reported method. [25] A calibration curve was plotted (R 2 = 0.994) with the series of gallic acid standards from which the total phenolic contents values were determined. Results are expressed as mg of gallic acid equivalents (GAE).…”
Section: Isolation Of Flower Extractmentioning
confidence: 99%
“…Also it is reported that polyphenolics can be extracted efficiently using water as extracting solvent which also increases the versatility of the process as it further minimizes the use of toxic solvents . The polyphenolics act as better green reducing agents for noble metal and other transition metal ions . Considering these aspects, we believe that the use of flower extract of Lantana camara as reducing‐cum‐stabilizing agent for the preparation of Pd NPs can provide a new platform to this noxious plant making it a value‐added weed for nanotechnology‐based industries in future.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations